Majapahit Excursion: Field School for History Students in Mojokerto City and Regency - Wahyudi, Deny Yudo; Jati, Slamet Sujud Purnawan; Wijaya, Daya Negri; Ikhrom, Anisa Musyaroful; Ananda, Labuda Shofiya (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This research aims to study the Majapahit Excursion as a field school model for history students to enhance academic competence and practical skills through the exploration of historical remains in Mojokerto, while also fostering imagination, learning motivation, and integration of local-national history. Methodology: This research uses a qualitative approach with a type of field study. The subjects of the study include students from Mojokerto. The research instruments consist of observation guidelines, interview guidelines, and documentation, while data collection techniques are conducted through participatory observation, in-depth interviews, and document analysis. Main Findings: Research findings indicate that the Majapahit Excursion program is capable of enhancing students' understanding of the archaeological remains of Majapahit, developing skills in toponymy analysis and local historical interpretation, strengthening collaborative abilities in the field, as well as introducing the local wisdom of the Majapahit Kingdom and its relevance in modern life. Novelty/Originality of this study: The novelty of this research lies in the formulation of a field school model based on the Majapahit heritage in Mojokerto, which not only focuses on strengthening historical theory but also on integrating students' empirical experiences with local history learning. This model can serve as a strategic alternative in the development of site-based history curriculum in Indonesia.